Development of a dietary supplement with iron oxide nanoparticles and study of its chronic toxicity and biological effects - A. S. Dydykin; E. R. Vasilevskaya; M. A. Aslanova; O. K. Derevitskaya; E. K. Polishchuk; N. V. Kupaeva; G. G. Moldovanov (Пищевые системы, 2025)
Anemia is a global public health problem, the main cause of which is iron deficiency in the body. The difficulty of enriching the diet with iron is explained by the oxidative nature of iron, which leads to undesirable sensory changes and a decrease in the quality and shelf life of food. The work is devoted to the selection of bioavailable forms of iron, which, when added to food in an appropriate amount, are not rejected by the body. The aim of the work was to study in experiments on laboratory rats the chronic toxicity and effectiveness of the developed dietary supplement “PoliFerVit” in comparison with commercial preparations of iron oxides E172 (Fe2O3 + FeO) and iron sulfate (FeSO4 × 7H2O). The objects of the study were iron (II) sulfate heptahydrate (FeSO4 × 7H2O), a mixture of iron oxides E172 (Fe2O3 + FeO), dietary supplement “PoliFerVit” for use as a source of iron (FeO, Fe2O3, Fe3O4), vitamin C, and dihydroquercetin. In the process of work, a biologically active food additive (dietary supplement) “PoliFerVit” was developed, the iron content in the additive is 136% of the daily requirement. A comparison of the biological activity and chronic toxicity of the dietary supplement “PoliFerVit” and commercial iron preparations showed that all studied objects, when administered daily to laboratory animals for 32 days, did not affect the body weight of animals and their physiological state, and also did not cause changes in the main indicators of the general blood test, in particular, in the leukocyte formula. The revealed dynamics towards an increase in serum iron content when using a mixture of iron oxides (up to 17%) and dietary supplement “PoliFerVit” (up to 22%) indicates similar bioavailability, and the bioavailability of dietary supplement “PoliFerVit” is higher, which is probably due to the nanoscale size of iron particles and the combined composition of the additive. An important advantage of the dietary supplement “PoliFerVit” is a less pronounced negative effect on the antioxidant system, which was expressed in an increase in the superoxide dismutase index to 44%.